Atom-by-atom analysis of sintering dynamics and stability of Pt nanoparticle catalysts in chemical reactions. (11th December 2020) - Martin, Thomas E.; Mitchell, Robert W.; Boyes, Edward D.; Gai, Pratibha L.
Abstract : Supported Pt nanoparticles are used extensively in chemical processes, including for fuel cells, fuels, pollution control and hydrogenation reactions. Atomic-level deactivation mechanisms play a critical role in the loss of performance. In this original research paper, we introduce real-time in-situ visualization and quantitative analysis of dynamic atom-by-atom sintering and stability of model Pt nanoparticles on a carbon support, under controlled chemical reaction conditions of temperature and continuously flowing gas. We use a novel environmental scanning transmission electron microscope with single-atom resolution, to understand the mechanisms. Our results track the areal density of dynamic single atoms on the support between nanoparticles and attached to them; both as migrating species in performance degradation and as potential new independent active species. We demonstrate that the decay of smaller nanoparticles is initiated by a local lack of single atoms; while a post decay increase in single-atom density suggests anchoring sites on the substrate before aggregation to larger particles. The analyses reveal a relationship between the density and mobility of single atoms, particle sizes and their nature in the immediate neighbourhood. The results are combined with practical catalysts important in technological processes. The findings illustrate the complex nature of sintering and deactivation. They are used to generate new fundamental insights into nanoparticle sintering dynamics at the single-atom level, important in the development of efficient supported nanoparticle systems for improved chemical processes and novel single-atom catalysis. This article is part of a discussion meeting issue 'Dynamic in situ microscopy relating structure and function'.